Infective endocarditis caused by Streptococcus acidominimus - Kabbara, Wissam K. (2019)
Purpose A case of infective endocarditis caused by Streptococcus acidominimus is reported. Summary An 81-year-old Caucasian man underwent an elective transcatheter aortic valve implantation due to his severe aortic valve stenosis. He presented to the hospital 3 weeks later with a 1-week history of fever (39ºC) that did not resolve following a 3-day course of azithromycin and a 5-day course of ciprofloxacin. Three sets of blood sample cultures were taken. Empirical antimicrobial treatment was initiated to target gram-positive and gram-negative microorganisms and consisted of vancomycin 1 g intravenous (i.v.) every 12 hours and imipenem–cilastatin 500 mg i.v. every 6 hours. After 48 hours, the blood culture was positive for S. acidominimus. The strain was sensitive to ampicillin, cephalosporins, tetracycline, and vancomycin. It was resistant to penicillin, macrolides, trimethoprim–sulfamethoxazole, and fosfomycin. Transesophageal echocardiography showed a small mobile vegetation attached to the anterior mitral valve leaflet, along with mild mitral regurgitation. The patient was diagnosed with native mitral valve infective endocarditis, and imipenem–cilastatin was discontinued. The patient showed clinical and laboratory improvement during his 2-week hospitalization. A peripherally inserted central catheter was put in place, and the patient was discharged on i.v. vancomycin to complete a total of 6 weeks treatment, after which the infection resolved. Conclusion An 81-year-old man diagnosed with mitral valve endocarditis caused by S. acidominimus was successfully treated with vancomycin.